Aseptic Meningitis as an Immune-Related Adverse Event after Pembrolizumab - Gian Lima; Adriana Kahn; Shashank Sama; Jacqueline Savage (Case Reports in Oncological Medicine)
Introduction. The management of patients with advanced malignancies is challenging, although recent advances with immunotherapy have shown better outcomes. Pembrolizumab has been associated with a variety of immune-related side effects, but the occurrence of aseptic meningitis is rare. Case. A 55-year-old male with a history of metastatic lung adenocarcinoma previously treated with pembrolizumab presented with persistent severe headaches and photophobia. Subsequent workup with cerebrospinal fluid analysis showed elevated opening pressure, increased nucleated cells with 30% lymphocytes, elevated protein levels, and normal glucose levels. The patient was started on high doses of IV steroids and progressed with significant improvement of his symptoms. Discussion. Given the rarity of this side effect, this case is a reminder that immune checkpoint inhibitors can cause aseptic meningitis and its early recognition is important for initiation of therapy with steroids and prompt discontinuation of the immunotherapy agent.